2000
DOI: 10.1063/1.480934
|View full text |Cite
|
Sign up to set email alerts
|

Four-component relativistic density functional calculations of heavy diatomic molecules

Abstract: Articles you may be interested inTime-dependent four-component relativistic density-functional theory for excitation energies. II. The exchangecorrelation kernel J. Chem. Phys. 123, 054102 (2005); 10.1063/1.1940609 Scalar relativistic all-electron density functional calculations on periodic systems J. Chem. Phys. 122, 084108 (2005); 10.1063/1.1851973 Response to "Comment on 'Four-component relativistic density functional calculations of heavy diatomic molecules'" [Comment on "Four-component relativistic densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 58 publications
(37 reference statements)
7
67
0
Order By: Relevance
“…(2) Relativistic DFT generally employs non-relativistic density functionals due to the limited availability of relativistic functionals [120][121][122][123][124][125]. However, computational studies [126][127][128] indicate that the effect of such relativistic corrections is negligible for spectroscopic constants. For core properties, here represented by the extreme case of the contact density, the situation is less clear.…”
Section: Calibration Of Contact Densitiesmentioning
confidence: 99%
“…(2) Relativistic DFT generally employs non-relativistic density functionals due to the limited availability of relativistic functionals [120][121][122][123][124][125]. However, computational studies [126][127][128] indicate that the effect of such relativistic corrections is negligible for spectroscopic constants. For core properties, here represented by the extreme case of the contact density, the situation is less clear.…”
Section: Calibration Of Contact Densitiesmentioning
confidence: 99%
“…In spite of various theoretical [41][42][43] and experimental [44][45][46][47][48] studies, the molecular properties of Pt 2 are not well known. In particular, the identity of the ground state electronic structure of this molecule is still unresolved, which leads to difficulty in interpreting experimental observations.…”
Section: E Ptmentioning
confidence: 99%
“…To improve DFT calculations, various theoretical aspects were introduced. To obtain better energy and geometrical results, dynamical and non-dynamic electron correlation was considered by Lee et al, [15] to obtain reliable spectroscopic data relativistic effects for binding energy for heavy metals were introduced by Varga et al, [9] and Grönbeck and Andreoni [10] studied neutral and anion various shapes to Pt 5 using SLDA and BLYP. Their calculations found that 3-D geometries are not favored up to Pt 5 clusters.…”
Section: De-ee0000466 Ballard Materials Products Incmentioning
confidence: 99%
“…[7,8] In particular, platinum nanoparticles, despite their high price, are considered as the catalyst of choice for fuel cell technology due to their excellent catalytic abilities. Therefore, theoretical and computational [9][10][11][12][13][14][15] investigations as well as experimental approaches [16][17][18] have been performed extensively to understand this material. The aim of this research is the maximizing of the benefit from the use of such precious metal and also understand the underpinning fundamentals of the observed properties.…”
Section: Introductionmentioning
confidence: 99%